An Appraisal of Economic Dimension in Nigeria’s Multilateral Diplomacy - Talibu , Oladimeji (Global Disclosure of Economics and Business, 2017)
Nigeria’s multilateral economic policy has come under scrutiny and criticism in recent years from policy quarters and informed publics. This becomes necessary because of the perceived policy discrepancy between policy intention and outcome. Most Nigerians, especially from the academia and policy quarters, continue to reassess Nigeria’s place in international institutions vis-à-vis its national goals and interests. This article is therefore an extension of such exercise, to assess and explore a section of Nigeria’s involvement in multilateral institutions since 1960, the year of independence. It explores and assesses the economic aspect of Nigeria’s multilateral policy and seeks to appraise what Nigeria has benefitted from its decades of involvement in multilateral organizations. In achieving this, the article uses latent content analysis to mine data from existing documents, journal articles, newspapers, and policy papers to dissect the process of multilateralism in Nigeria’s foreign policy. In addition, the article takes into consideration the use of hermeneutics approach, which is premised on the interpretation of all available evidence, to arrive at objectivity.